The quality of reports of randomised trials in 2000 and 2006: comparative study of articles indexed in PubMed - Hopewell, S; Dutton, S; Yu, L-M; Chan, A-W; Altman, DG (BMJ Publishing Group, 2010)
Objectives To examine the reporting characteristics and methodological details of randomised trials indexed in PubMed in 2000 and 2006 and assess whether the quality of reporting has improved after publication of the Consolidated Standards of Reporting Trials (CONSORT) Statement in 2001.